2012
DOI: 10.1086/668900
|View full text |Cite
|
Sign up to set email alerts
|

Show Me the Honey! Effects of Social Exclusion on Financial Risk-Taking

Abstract: This research examines the effects of social exclusion on a critical aspect of consumer behavior, financial decision-making. Specifically, four lab experiments and one field survey uncover how feeling isolated or ostracized causes consumers to pursue riskier but potentially more profitable financial opportunities. These daring proclivities do not appear driven by impaired affect or self-esteem. Rather, interpersonal rejection exacerbates financial risk-taking by heightening the instrumentality of money (as a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(149 citation statements)
references
References 42 publications
(60 reference statements)
4
135
1
Order By: Relevance
“…Second, it tested whether increased desires to connect to nature mediated the effect of ostracism on ecological behavior. To manipulate ostracism, participants recalled a past ostracism or physical pain experience (e.g., Chen, Williams, Fitness, & Newton, 2008;Duclos, Wan, & Jiang, 2013). Next, participants reported their desires to connect to nature and their inclinations to behave ecologically.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, it tested whether increased desires to connect to nature mediated the effect of ostracism on ecological behavior. To manipulate ostracism, participants recalled a past ostracism or physical pain experience (e.g., Chen, Williams, Fitness, & Newton, 2008;Duclos, Wan, & Jiang, 2013). Next, participants reported their desires to connect to nature and their inclinations to behave ecologically.…”
Section: Methodsmentioning
confidence: 99%
“…In the first part, participants completed a memory task by recalling a past experience to induce feelings of ostracism (e.g., Chen et al, 2008;Duclos et al, 2013). Participants were instructed to describe these experiences in as much detail as possible.…”
Section: Procedures and Materialsmentioning
confidence: 99%
“…Excluded consumers have been found to seek uniqueness (Wan, Xu, and Ding 2014;Tian, Bearden, and Hunter 2001), take more risks (Duclos, Wan, and Jiang 2013), and exhibit more switching behavior (Su et al 2017), all in the service of restoring their self-view. All of these effects could explain switching from the status quo (e.g., the United Kingdom as a member of the European Union) to an unknown future (Brexit).…”
Section: Why Do People Sometimes Vote Against Their Self-interest?mentioning
confidence: 99%
“…For example, Duclos et al (2013) demonstrated that there is an increasing interest in exploring the influence of social exclusion on behavioral decisions, especially consumer decisions. In this study, we identified the money-seeking tendency of men and the attention-seeking tendency of women who face social exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…In line with social exclusion tending to increase self-focus and strengthen self-belief in men, money can be an effective tool to bolster one's agentic beliefs because it is closely related to a sense of control over one's life (Johnson & Krueger, 2006) and is an effective substitute for popularity (Duclos, Wan, & Jiang, 2013). Money acts as a powerful resource and is commonly considered as a symbol of competence and achievement.…”
Section: Salary Preference and Conspicuous Preferencementioning
confidence: 99%